A framework for successful SOA adoption in selected South African universities - Jacobs, Carmen (Rhodes University, Faculty of Commerce, Department of Information Systems)
The demand for systems iÂ·ntegration has become more and more significant in higher education as institutions want systems that provide coherent information with data that is up to date and not redundant and can seamlessly support the end user experience. Institutions have become more reliant on information systems to support both administrative functions and those involved in teaching, learning and research, but because each department supports a diverse array of computing platforms and applications, it becomes very difficult to integrate these systems. SOA is classified as an innovative approach to integrating existing systems involving the use of independent services that can be accessed without knowledge of the underlying platform implementation. Unfortunately, the SOA initiative will not be success if it is not understood and used correctly by various applications and systems throughout the organisation. SOA introduces complexity and challenges in systems integration, acceptance, governance, data, development planning, security and external opportunities. If an organisation does not embrace or enable change in each of these areas, it is not ready for the adoption of SOA. This research investigates the systems integration challenge in selected South African universities and explores factors for SOA adoption. The framework for the adoption of SOA comprises seven factors, of which Systems Integration is the most significant and represents an efficient starting point for institutions considering SOA adoption. Acceptance, Governance, Data, Development Planning, Security and External Opportunities are other factors of SOA adoption that require careful and thorough consideration before an institution can successfully adopt SOA. The results of this research emphasise the importance of being able to embrace change and innovation and modify strategies in order to reflect the constant changes required for the adoption of SOA.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: System analysis -- Data processing; System design -- Data processing; Systems integration; Service-oriented architecture (Computer science); Education, Higher -- Data processing